2023
DOI: 10.31219/osf.io/a86gq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Map of Spatial Navigation for Neuroscience

Abstract: An animal's ability to navigate space is crucial to its survival. It is also cognitively demanding, and relatively easy to probe. For these reasons, spatial navigation has received a great deal of attention from neuroscientists, leading to the identification of key brain areas and the ongoing discovery of a ``zoo'' of cell types responding to different aspects of spatial tasks. Despite this progress, our understanding of how the pieces fit together to drive behavior is generally lacking. We argue that this is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 419 publications
0
1
0
Order By: Relevance
“…The identification of specific neurons such as grid cells, headdirection cells, and boundary vector cells within the MEC, together with egocentrically modulated border cells in the LEC, furnishes empirical backing for these findings. Grid Cell Grid cells create a structured hexagonal lattice in two-dimensional spaces, serving as an allocentric spatial coordinate system within the brain, 9 which aids vector-based navigation. 10 These cells are organized into modules characterized by their spacing and orientation, with the spacing between these modules increasing by a ratio nearly equivalent to √2 , as illustrated in Figure 2C.…”
Section: Spatial Representations Within the Entorhinal Cortexmentioning
confidence: 99%
“…The identification of specific neurons such as grid cells, headdirection cells, and boundary vector cells within the MEC, together with egocentrically modulated border cells in the LEC, furnishes empirical backing for these findings. Grid Cell Grid cells create a structured hexagonal lattice in two-dimensional spaces, serving as an allocentric spatial coordinate system within the brain, 9 which aids vector-based navigation. 10 These cells are organized into modules characterized by their spacing and orientation, with the spacing between these modules increasing by a ratio nearly equivalent to √2 , as illustrated in Figure 2C.…”
Section: Spatial Representations Within the Entorhinal Cortexmentioning
confidence: 99%
“…Spatial navigation and reversal learning (RL) are fundamental skills for mobile animals. Spatial navigation involves identifying and maintaining a path between two locations [15]. Research over the past 50 years has identified key brain regions for spatial navigation in the medial temporal lobe and spatially selective cells like place cell (PC) [14], boundary cells (BC) [10], and head direction cells [17].…”
Section: Introductionmentioning
confidence: 99%